Consommation et modes de vie dans le mouvement des travailleurs desocupados en Argentine (2003-2007) - Pía V. Rius (Centre de Recherches sur les Mondes Américains, 2014)
This article explores a variety of consumptions’ practices observed within unemployed workers’ organizations (MTD) in Argentine from 2003 to 2007. Groups studied here where formed in 2002 when workfare programs were generalized. Relationship among these collectives’ members are seen through the process of administration of resources which remains little studied. Through the analysis of daily commitment in popular canteens and more generally, the use done of collectively obtained resources, it appears a form of citizenship based on forms of consumption. Production and consumption are thus associated as well as the division of labor observed within the members and in the relationship established with their environment.